Correlation of Hand-held Dynamometer and Isokinetic Dynamometer for Determining Quadriceps Index in Post-operative Anterior Cruciate Ligament Reconstruction - J. Wongcharoenwatana (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2019 Background: Quadriceps strength is a key factor in determining rehabilitation progression and the return to sports for patients with anterior cruciate ligament (ACL) reconstruction. Muscle strength can be measured with isokinetic dynamometers (ISOs) or hand-held dynamometers (HHDs). Objective: To ascertain the correlation between the quadriceps index (QI) derived from ISO and HHD measurements of post-operative ACL reconstruction patients, and to compare the sitting and prone positions for quadriceps strength assessments using HHDs. Materials and Methods: Patients who underwent ACL reconstruction over 3 months beforehand were included. Quadriceps strengths were ascertained with an ISO by 1 examiner with patients seated, and with an HHD by 2 examiners with patients seated and prone. QI is the quadriceps strength value of the involved leg expressed as a percentage of that of the uninvolved leg. The correlations between the QI values of each ISO and HHD setting were established. Results: Sixty patients, averaging 29.6 years of age, were evaluated. The intraclass correlation coefficient (ICC) of the inter-examiner reliability between the ISOs and HHDs by two examiners were 0.59 and 0.43 (sitting position), and 0.40 and 0.24 (prone position). The ICC of the inter-examiner reliability between the HHD results of two examiners was 0.60 for sitting position and 0.43 for prone position. Conclusion: The QIs obtained using HHDs with patients in sitting position had a poor-to-moderate correlation with those from ISOs. Moreover, the QIs procured using HHDs had a higher correlation with those from ISOs when patients were seated compared to when they were prone.